Analyzing the Effect of Drainage on the Stability of Tailings Dams Using the Interpretation of Cross-Correlations - Moustafa Hamze-Guilart; Lineu Azuaga Ayres da Silva; Anna Luiza Marques Ayres da Silva; Maria Eugenia Gimenez Boscov (Sensors)
Over the years, multiple tailings dam failures all over the world have been primarily linked to drainage issues. Given its critical role in dam stability, this research analyzes the relationship between precipitation, reservoir levels, and geotechnical instrumentation measurements along the elevation stages of a tailings dam. To assess the influence of drainage on dam performance, its dependence on infiltration, reservoir water fluctuations, and geotechnical instrumentation responses was modeled and interpreted. By applying time series analysis methods to the instrumentation data, including autocorrelation and cross-correlation functions, this study identifies patterns in drainage efficiency and its impact on stability. The time series data were regularized and transformed into stationary forms to ensure consistency in the analysis. Autocorrelation functions and cross-correlations between different monitoring instruments were computed specifically for the second to the seventh elevation stages of the tailings dam. This study focuses on four cross-sections of the dam, analyzing their behavior to differentiate the spatial and temporal effects of drainage. The results reveal variations in drainage efficiency across these different sections and elevation stages, providing a deeper understanding of the role of drainage in maintaining stability. The proposed methodology can also be successfully applied to other tailings storage facilities, such as tailings dams built downstream or dry stacking piles, contributing to improved monitoring and risk assessment strategies.